Made in Basel? A commentary on the contemporary art world in Asia. (1st October 2018) - Waters, Matthew J.
Abstract : Purpose: The purpose of this paper is to assess the recent emergence of contemporary art in Asia from a macro, sociocultural perspective. Design/methodology/approach: This commentary is based on secondary research and recent visits to contemporary art centres in major cities across Asia. Findings: The author argues that contemporary art in Asia emerges by extension of the Western contemporary art world and suggests that more must be done if Asia is to create a contemporary art world that is both internationally recognised and distinct from its Western precedent. Originality/value: This commentary debunks the hyperbole surrounding contemporary art in Asia as a regional phenomenon and provides a critical examination of the global (power) dynamics at play.